Genetic Characterisation of the upp Gene in Bifidobacterium bifidum PRL2010 - Giulia Longhi; Silvia Petraro; Christian Milani; Chiara Tarracchini; Chiara Argentini; Laura Maria Vergna; Gabriele Andrea Lugli; Leonardo Mancabelli; Ciaran Lee; Francesca Turroni; Douwe vanSinderen; Marco Ventura (Microbial Biotechnology)
ABSTRACT Bifidobacteria are key members of the human gut, especially during infancy. The ability of bifidobacteria to outcompete other members of the microbial communities encountered in this highly competitive human gut environment represents a key example of their evolutionary and ecological success. In the current report, we investigated the highly conserved bifidobacterial upp gene, which encodes the uracil phosphoribosyltransferase and which is involved in the pyrimidine salvage pathway. Phylogenetic analysis incorporating 107 bifidobacterial upp sequences, representing all currently known Bifidobacterium taxa, indicates that this gene followed an evolutionary route that apparently deviates from that of the 16S rRNA gene. In addition, the upp gene may support bifidobacterial survival in environments with limited uracil availability, potentially providing a competitive advantage under nutrient‐restricted conditions.